Complex DNA repair pathways as possible therapeutic targets to overcome temozolomide resistance in glioblastoma - Yoshimoto, Koji; Mizoguchi, Masahiro; Hata, Nobuhiro; Murata, Hideaki; Hatae, Ryusuke; Amano, Toshiyuki; Nakamizo, Akira; Sasaki, Tomio (Frontiers in Oncology, 2012)
Many conventional chemotherapeutic drugs exert their cytotoxic function by inducing DNA damage in the tumor cell. Therefore, a cell-inherent DNA repair pathway, which reverses the DNA-damaging effect of the cytotoxic drugs, can mediate therapeutic resistance to chemotherapy. The monofunctional DNA-alkylating agent temozolomide (TMZ) is a commonly used chemotherapeutic drug and the gold standard treatment for glioblastoma. Although the activity of DNA repair protein O6-methylguanine-DNA methyltransferase (MGMT) has been described as the main modulator to determine the sensitivity of glioblastoma to TMZ, a subset of glioblastoma does not respond despite MGMT inactivation, suggesting that another DNA repair mechanism may also modulate the tolerance to TMZ. Considerable interest has focused on MGMT, mismatch repair (MMR), and the base-excision repair (BER) pathway in the mechanism of mediating TMZ resistance, but emerging roles for the DNA strand-break repair pathway have been demonstrated. In the first part of this review article, we briefly review the significant role of MGMT, MMR, and the BER pathway in the tolerance to TMZ; in the last part, we review the recent publications that demonstrate possible roles of DNA strand-break repair pathways, such as single-strand break (SSB) repair and double-strand break (DSB) repair, as well as the Fanconi anemia pathway in the repair process after alkylating agent-based therapy. It is possible that all of these repair pathways have a potential to modulate the sensitivity to TMZ and aid in overcoming the therapeutic resistance in the clinic.